Modernization of the District Heating Systems in Ukraine : Heat Metering and Consumption-Based Billing - Semikolenova, Yadviga; Pierce, Lauren; Hankinson, Denzel (Washington, DC: World Bank, 2014)
District heating (DH) plays a critical role in meeting basic heating needs in Ukraine, but the sector faces serious challenges that must be resolved to avoid collapse. For DH companies, the primary concern is financial sustainability. Companies lack the revenue to invest adequately in DH networks leading to lower quality of service and higher operating costs. For customers, the primary concern is quality of service and affordability. Artificially low prices have resulted in the continued deterioration of DH supply assets (and gas supply assets) resulting in lower heat supply quality. Low DH prices have provided little incentive for investment in energy efficiency. As a result, Ukraine is one of the highest energy intensive countries in the world. Ukraine, together with other Former Soviet Union countries, did not follow the path chosen by their neighbors to modernize their DH sectors. Many countries of Eastern Europe enacted critical reforms in the 1990s to address problems related to affordability, quality of service, and financial sustainability similar to those now facing Ukraine. Evidence from these countries suggests that these challenges currently facing Ukraine, while difficult, are far from insurmountable. This study situates heat metering and consumption-based billing in the context of the various DH sector reforms needed in Ukraine. It builds on the work of previous studies including the recommendations of the 2010 Energy Sector Management Assistance Program (ESMAP)-funded study, prepared by the World Bank that identified how to improve the DH sector in Kharkiv. That study outlined the potential for investments in DH systems in Kharkiv and other similar cities in Ukraine in both heat supply and demand side. It also recognized that policy changes needed to be initiated in order to create the enabling environment for this potential to be realized.